European citizens’ worries and self-responsibility towards climate change - Mata, F.; Jesus, M. S.; Cano-Díaz, C.; Dos-Santos, M. J. P. L. (Sustainability, 2023)
Attitudes and perceptions about climate change (CC) are crucial to public engagement and support in the promotion of mitigating actions and sustainable lifestyles embracing the United Nations’ sustainable development goals. This study aimed to investigate how worried are European citizens about CC, and what is their willingness to assume self-responsibility in its mitigation. We used the European Social Survey, namely the answers to the questions “How worried are you about climate change?” and “To what extent do you feel a personal responsibility to try to CC?” and have related them with demography and individual perception of the society and its policies. We fit two statistical models to each of the questions studied and found the following: Model 1—people that trust in scientists are more worried about CC, people satisfied with the national government are more worried about CC, women are more worried about CC than men, and older and more educated people are also more worried about CC; Model 2—Women have higher levels of self-responsibility, people that trust in scientists feel more responsibility when satisfied with the economy and the health system of the country, and older people that trust in scientists also have more responsibility.